EVALUATION OF MORBIDITY AND MORTALITY OF THE NEWBORN ADMITTED TO SPECIAL NEWBORN CARE UNIT - KIREETI, A S; KUMAR, B SASI; YENEPALLI, MRUDULA; PULAGANTI, MADHUSUDANA; MADHAVI, MEENAKSHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Under the facility-based newborn care scheme (FBNC), special newborn care units (SNCUs) are being established in India with the primary motto of reducing the neonatal mortality rate (NMR). Methods: The present study was a retrospective study conducted for 2 years to gain knowledge of the functioning of SNCU, and its morbidity and mortality pattern of sick newborn attending were evaluated in the present research. The study was conducted at SNCU, SVRRGGH, Tirupati. The total admissions were male, referrals from outside facilities, and low birth-weight newborns. Results: The overall leading cause of admissions was birth asphyxia-related morbidity (BA) (24%), infections (22.2%), followed by respiratory distress syndrome (RDS) (15.3%). The causes of mortality were BA (33.2%), followed by RDS (27%) and infections (16.4%). The case fatality rates of RDS (45%) were the highest, followed by meconium aspiration syndrome (40%) and BA (35.6%). Although morbidity was high, case-fatality rate of infections (16.4%) was low. Conclusion: This study has highlighted the deficiencies at SNCU influencing the outcome of admitted newborns, thus guiding steps for improvisation.